Selective adsorptive removal and separation of harmful anionic dyes using mesoporous magnesium oxide-chitosan composite - Mudita Nagpal; Nidhi Sharma; Ankit Mittal (Hybrid Advances)
In this study, mesoporous magnesium oxide-chitosan composite (MCC) has been studied for the selective adsorptive separation of harmful anionic dyes. The synthesis of MCC has been carried out via a post-immobilization method, which involves combining chitosan with pre-fabricated MgO at room temperature. MgO used for preparing MCC has been prepared via an environmental friendly precipitation procedure, with template, gelatin. Characterization techniques such as XRD, SEM and FTIR validated the presence of chitosan and MgO in MCC. BET surface area of MCC has been evaluated as 35.6 m2 g−1, using N2 adsorption-desorption isotherms. BJH analysis showed that mesopores are present in the composite. Synthesized composite, MCC has been shown to be excellent for adsorption of toxic anionic dyes, like Congo red (CR) and Indigo carmine (IC). The impact of multiple adsorption parameters such as, pH, time of contact, dosage of adsorbent and concentration of dye, on CR adsorption on MCC has been studied in detail. The maximum adsorption capacity shown by MCC for CR has been reported to 156.25 mg g−1. Further, MCC exhibits good recyclability and a selectivity for anionic dyes by effectively adsorbing anionic dyes from binary systems composed of anionic and cationic dyes, with a high value of separation factor.